A Prospective Comparative Study of Renal Function in Live Renal Donors Who Underwent Open and Laparoscopic Nephrectomy - Farshid, Saman; Tayyebi Azar, Ali; Habibi, Behnam; Pasha, Alireza (Urology Journal, 2026)
Introduction: Open nephrectomy surgery in a kidney donor involves pain and many risks after the surgery, which leads to the inability to perform normal activities. For this reason, today the laparoscopic nephrectomy method is preferred in order to avoid complications and to return to normal life sooner. However, it is very critical to assess the impact of modifying the surgical technique on the outcome of kidney donation. Thus, the present study was undertaken with the following specific objective: a comparative study of the renal profile of live kidney donors who have undergone open and laparoscopic nephrectomy. Materials and Methods: The study in the present report was cross-sectional in nature. Participants included 91 kidney donors who had undergone either open nephrectomy (n = 46) or laparoscopic nephrectomy (n = 45). Data on the level of initial basic renal function, the duration of surgery, and the duration of hospitalization, together with the course of renal function in the 6 months after surgery, were collected. The data were analyzed using the Statistical Package for the Social Sciences, version 27 (SPSS version 27). Results: The mean age of kidney donors was 29.4 ± 4.8 years, and all patients were male (100%). Body mass index and weight were comparable between the open and laparoscopic nephrectomy groups, with no statistically significant differences (P > 0.05). The mean duration of surgery in the open nephrectomy group (2.37 ± 0.30 hours) was significantly shorter than that in the laparoscopic group (3.37 ± 0.13 hours) (P < 0.001). The mean length of hospital stay was significantly shorter in the laparoscopic group (3.31 ± 0.31 days) compared to the open group (4.06 ± 0.04 days) (P < 0.001). GFR decreased significantly in both groups at discharge and 6 months postoperatively compared to baseline (paired t-test, all P < 0.001), but there was no significant difference in GFR between groups at any time point (P > 0.05). Both groups experienced a significant postoperative decline in hemoglobin, with a greater reduction in the open group (−1.59 ± 0.79 g/dL) compared to the laparoscopic group (−1.05 ± 0.95 g/dL) (P = 0.004). White blood cell counts increased postoperatively in both groups, with no significant difference between them (P = 0.118). Surgical complications included transection of the superior polar artery in 5.5% of cases. Conclusion: In laparoscopic nephrectomy, the time of surgery is longer, but the days of hospitalization after surgery do not differ and do not negatively affect the return of donor kidney function compared to the open method. Moreover, post-surgical problems have not been very frequent and are manageable in the best way possible.